OPPORTUNITIES AND CHALLENGES OF AI INTEGRATION IN ISLAMIC EDUCATION MANAGEMENT TOWARDS OBE CURRICULUM - Husnani Husnani; Multi Efrini; Benny Apero; Riefli Fatmi; Nur Azizah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Artificial intelligence (AI) is rapidly reshaping higher education, and Islamic Education Management (MPI) programs are no exception. At the same time, the global move towards Outcome-Based Education (OBE) demands a more measurable, student-centered approach to learning. However, little attention has been paid to how these two forces—AI and OBE—can work together within the unique context of Islamic higher education. This study seeks to fill that gap by exploring the opportunities and challenges of integrating AI into MPI programs transitioning towards OBE-based curricula. Using a library-based research method, this study draws on academic journals, conference proceedings, and policy documents published between 2020 and 2026. The findings suggest that AI holds considerable promise: it can personalize learning pathways, automate routine administrative tasks, support data-driven assessment of student outcomes, and strengthen institutional quality assurance for global recognition. However, these benefits are accompanied by real challenges, including inadequate digital infrastructure, limited AI competence among educators, concerns over data privacy and algorithmic bias, and a deeper tension between AI-driven efficiency and the spiritual, humanistic values at the heart of Islamic education. Beyond identifying these opportunities and challenges, this study offers practical guidance for MPI leaders, policymakers, and curriculum designers. It proposes a phased integration model with three key pillars: building human capacity, developing ethical AI frameworks aligned with Islamic values, and fostering institutional collaboration. Ultimately, this study argues that the path to global recognition for MPI programs lies not in rushing technological adoption but in pursuing a strategic, gradual, and value-centered transformation that preserves the essence of Islamic education while embracing the benefits of digital innovation.